Fatty liver indices in obese and non-obese patients with dyslipidemia - Peličić, Milena; Petrović, Milica; Popović, Ljiljana (Medicinski podmladak, 2024)
Introduction: The obesity pandemic is closely related to the growing prevalence and severity of fatty liver. Metabolic imbalances – insulin resistance and dyslipidemia – are cited as the main factors that create the basis for its occurrence and progression to non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH) and other complications (cirrhosis, hepatocellular carcinoma). Aim: The aim of the study was to compare the FLI and TyG indices within two groups of patients, obese and non - obese, as well as to determine their interrelationship and correlation with other laboratory parameters. Material and methods: The study included 62 patients, divided into two groups: obese and non-obese, equally represented (50%; 31). Anthropometric measurements and all laboratory tests of blood samples taken after 12 – 14 hours of night fasting were performed at the Clinic for Endocrinology, Diabetes and Metabolic Diseases UCCS. The FLI and TyG indices were calculated using appropriate algorithmic calculators. Results: The median of FLI in the obese patients was 86.4 and in the non-obese 13.7 (p<0.001). The average value of TyG in obese was 5.0 ± 0.3 and in the non-obese 4.7 ± 0.3 (p<0.001). Obese patients were significantly older, had higher BMI and waist circumference (p<0.01). Non-obese patients had higher values of total cholesterol, HDL and LDL (p<0.05), while tryglicerides were higher in obese patients (p=0.01). The interrelationship as well as the correlation between indices and other laboratory parameters was of a significant medium degree (p<0.05), except in the case of HDL, where a moderate degree of negative correlation was observed. Conclusion: Fatty liver indices were significantly higher in obese patients. Total cholesterol, HDL and LDL were higher in non-obese and tryglicerides were higher in obese patients. The interrelationship and correlations between the indices and other laboratory parameters were moderately positive. Lower HDL values resulted in higher indices values. Key words: obesity, FLI, TyG, NAFLD.